3D‐Printed Cathodes of LiMn1−xFexPO4 Nanocrystals Achieve Both Ultrahigh Rate and High Capacity for Advanced Lithium‐Ion Battery. Issue 18 (23rd June 2016) - Hu, Jiangtao; Jiang, Yi; Cui, Suihan; Duan, Yandong; Liu, Tongchao; Guo, Hua; Lin, Lingpiao; Lin, Yuan; Zheng, Jiaxin; Amine, Khalil; Pan, Feng
Abstract : A 3D‐printing technology and printed 3D lithium‐ion batteries (3D‐printed LIBs) based on LiMn0.21 Fe0.79 PO4 @C (LMFP) nanocrystal cathodes are developed to achieve both ultrahigh rate and high capacity. Coin cells with 3D‐printed cathodes show impressive electrochemical performance: a capacity of 108.45 mAh g −1 at 100 C and a reversible capacity of 150.21 mAh g −1 at 10 C after 1000 cycles. In combination with simulation using a pseudo 2D hidden Markov model and experimental data of 3D‐printed and traditional electrodes, for the first time deep insight into how to achieve the ultrahigh rate performance for a cathode with LMFP nanocrystals is obtained. It is estimated that the Li‐ion diffusion in LMFP nanocrystal is not the rate‐limitation step for the rate to 100 C, however, that the electrolyte diffusion factors, such as solution intrinsic diffusion coefficient, efficiency porosity, and electrode thickness, will dominate ultrahigh rate performance of the cathode. Furthermore, the calculations indicate that the above factors play important roles in the equivalent diffusion coefficient with the electrode beyond a certain thickness, which determines the whole kinetic process in LIBs. This fundamental study should provide helpful guidance for future design of LIBs with superior electrochemical performance. Abstract : 3D lithium‐ion batteries (LIBs) based on LiMn0.21 Fe0.79 PO4 @C (LMFP) nanocrystals with 3D printing technology are developed. The 3D‐printed electrode battery delivers 108.45 mAh g −1 at 100 C, ranking it the highest rate capability among LMFP LIBs. Through further numerical simulations, the influence of electrolyte diffusion factors on the battery rate performance is illustrated.